2011
DOI: 10.1021/ma200621r
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Polymer Tethered Highly Grafted Nanoparticles

Abstract: Spherical nanoparticles of silica grafted with a dense brush of low-polydispersity polymers prepared by living radical polymerization are shown to form ordered crystalline structures. The minimum distance between nanoparticle surfaces, a good measure of the end-to-end distance of the tethered polymers, scales as the square root of the molecular weight of the polymer chains. The blending of the grafted nanoparticles with homopolymers of matched and mismatched molecular weights indicates that the crystalline ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
76
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 47 publications
8
76
0
Order By: Relevance
“…Thermal cleavage of the tethering point restored the T g to that of the bulk, implying the suppression was due to excess free volume arising from frustrated chain packing. Packing frustration due to interstitial spaces within HNP assemblies that were pointed out by Yu and Koch [29] should have a profound impact on other collective relaxation modes, such as physical aging. Such detailed studies on HNP assemblies, crucial for long-term use assessments and processing procedures to tune order (i.e.…”
Section: Dynamics Of Hnps and Hnp Assembliesmentioning
confidence: 96%
See 2 more Smart Citations
“…Thermal cleavage of the tethering point restored the T g to that of the bulk, implying the suppression was due to excess free volume arising from frustrated chain packing. Packing frustration due to interstitial spaces within HNP assemblies that were pointed out by Yu and Koch [29] should have a profound impact on other collective relaxation modes, such as physical aging. Such detailed studies on HNP assemblies, crucial for long-term use assessments and processing procedures to tune order (i.e.…”
Section: Dynamics Of Hnps and Hnp Assembliesmentioning
confidence: 96%
“…2(b)]. [29] The bulk materials are solids with elastic relaxation times greater than 10 5 s, while the hair, when unattached to particles, show liquid behavior with relaxation times less than 1 s. The bulk material shows a distinct yield stress, much like colloidal crystals or ordered BCP structures. [30] As the interaction potential between adjacent HNPs would not only affect the structure but also the elastic properties, they examined the scaling of the elastic modulus with the molecular weight of the polymer (and hence the radius) and determined that the repulsive potential scales as U(r) ∝ r −12.5±2…”
Section: Structure Of Hnps and Hnp Assembliesmentioning
confidence: 99%
See 1 more Smart Citation
“…Goel and coworkers (Goel et al 2011) studied the structure of polymer-tethered highly grafted nanoparticles. The nanoparticles crystallized into highly ordered crystal structures (FCC) as measured by small angle X-ray scattering (Fig.…”
Section: Role Of Polymer-graft Modification On the Interaction Dynammentioning
confidence: 99%
“…Computational 6,7,9,12,16,[18][19][20][21][24][25][26][27]33 and experimental 3,4,10,13,14,22,[28][29][30][31]35,40 studies on nanocomposites, consisting of homopolymer-functionalized nanoparticles in a polymer matrix, have demonstrated that the chemistry and relative molecular weights of the graft and matrix polymers, grafting density, and nanoparticle size are parameters that play a critical role in dictating the spatial organization of the nanoparticles. For example, experimental studies 30,42,43 have achieved the migration of the polymer-grafted nanoparticles from one domain to another domain in the matrix by thermally changing the chemistry of the grafted homopolymers on the nanoparticle, and thus the compatibility of the grafted polymer and matrix.…”
mentioning
confidence: 99%